TRANSABDOMINAL ECHO-GUIDED FINE NEEDLE BIOPSY WITHOUT ASPIRATION IN THE DIAGNOSIS OF CANINE PROSTATIC NEOPLASIA - Grandez R., Ricardo (2013)
Fine-needle aspiration biopsy guided with trans-abdominal ultrasound is a safe and minimally invasive technique that is used to confirm the diagnosis of prostatic neoplasia. A variation of this technique is a fine-needle biopsy without aspiration in which negative pressure is not exerted when obtaining the material. Four cases with clinical and ultrasound alterations compatible with prostatic neoplasia were evaluated with ultrasound-guided fine-needle biopsy without aspiration as a diagnostic tool. The procedure was done with conventional ultrasound guidance. When the area of interest was found, an ultrasoundguided sample collection was performed using a 21G x 1½” needle. The sample was expelled through the needle with a syringe onto a glass slide and stained using Tinción 15®. Sample interpretation was based on the identification of tumor cells and general criteria of malignancy. Ultrasound-guided fine-needle biopsy without aspiration as a diagnostic tool allowed obtaining sufficient quantity of biological material with minimal blood contamination and formation of artifacts, and appropriate conservation of cellular morphology to perform suitable interpretation and cytological diagnosis of prostatic neoplasia.